2009
DOI: 10.1007/s11661-009-0069-x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Constituent Materials on the Impact Toughness and Fracture Mechanisms of Hot-Roll-Bonded Aluminum Multilayer Laminates

Abstract: Two aluminum multilayer laminates have been processed by hot roll bonding following similar processing paths. The first one is constituted by alternated Al 2024 and Al 1050 layers (ALH19) and the second one by alternated Al 7075 and Al 1050 layers (ADH19). The influence of the constituent materials in the multilayer laminates both during the processing at high temperature and during the subsequent mechanical characterization has been analyzed. The mechanical behavior of the as-received materials at the process… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(14 citation statements)
references
References 25 publications
0
11
0
3
Order By: Relevance
“…According to this study, the impact toughness of the laminate was improved by increasing the number of layers and optimizing the interfacial adhesion [10]. Studying the fracture behavior of a series of Al laminates, Jimenez et al [5,8,9,11] claimed that toughness enhancement in laminates was the result of energy consumption by delamination at the interfaces, renucleation of crack in the following layers and plastic deformation of the ductile layers. According to their hypothesis, delamination at the interface can improve toughness by reducing crack tip triaxiality and redistribution of the local stresses.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…According to this study, the impact toughness of the laminate was improved by increasing the number of layers and optimizing the interfacial adhesion [10]. Studying the fracture behavior of a series of Al laminates, Jimenez et al [5,8,9,11] claimed that toughness enhancement in laminates was the result of energy consumption by delamination at the interfaces, renucleation of crack in the following layers and plastic deformation of the ductile layers. According to their hypothesis, delamination at the interface can improve toughness by reducing crack tip triaxiality and redistribution of the local stresses.…”
Section: Introductionmentioning
confidence: 95%
“…Among different materials introduced for multilayer fabrication, aluminum alloys are preferred candidates due to their reasonable mechanical properties and low cost [5]. Studies have shown that aluminum laminates are capable to enhance mechanical behavior of their constituent materials [1,[7][8][9][10]. For example, Alic and Danesh [1] reported R curve behavior in an Al laminate, while such a behavior was not seen in the monolithic material.…”
Section: Introductionmentioning
confidence: 99%
“…En un artículo anterior [18] , donde se estudió la influencia del aluminio puro 1050 constreñido entre dos aleaciones de aluminio de alta resistencia, se observó que la extensión del gradiente de elementos aleantes determina las propiedades mecánicas de las aleaciones constituyentes cerca de la intercara. Como ya se ha mencionado, la presencia de precipitados MgZn 2 es la principal responsable de las propiedades mecánicas de la aleación Al 7075.…”
Section: Gradientes De Composición Y Ensayo De Microdureza Vickersunclassified
“…These included, for instance, titanium alloy/steel, 2-3 aluminum alloy/aluminum alloy, 4 aluminum alloy/steel, 5 brass/steel, 6 steel/steel [7][8][9] and other possible combinations. 10 Laminated metallic composites offer an abundance of topics for study, ranging from fabrication, where the flow of layers during deformation can be explored, [11][12][13] through their overall mechanical properties 14 measured, for instance, by conventional tension testing 10,15 or by three-point bend test; 16,17 used for mapping delamination during failure.…”
Section: Introductionmentioning
confidence: 99%